The Development System of Linguistic Experience on The Debate Text of Presidential Candidate of The Republic of Indonesia 2014 – 2019 (e-Journal of Linguistics, 2019)
The presidential candidate debate text development system is a sort of linguistic experienceelements reflecting the speaker's way of thinking related to the policies of the nation and state. The textdevelopment might indicate the policy intended by a presidential candidate to build the nation and state.Based upon this, there are three factors behind the selection of this topic to research; namely, empirical,practical, and theoretical factors. This study is conducted aimed at describing various issues concerningthe development of the linguistic experience of the two presidential candidates in improving the nationaland international welfare and international politics-national resilience. Systemic Functional Linguistic(SFL) theory initiated by Halliday (1985,1991, 2004, 2014) is used as the grounded theory in this study.This study employs qualitative descriptive approach with linguistic phenomenological paradigm. Variousdata types analyzed in this study include words, phrases, clauses, group phrases, and text units. The datause taken from the recorded of audio-visual Candidate Debate Text (CDT) in stage I and II. The researchinstruments used in this study are text validation tables and contexts. Along with some advancedtechniques, documentation and observation were conducted to collect the data. Meanwhile, in processingthe data collected, this study passed several stages; namely, data classification, segmentation, andcodification. To analyze the data processed, this study employed several stages namely reduction,presentation, and verification. The results of this study show that Prabowo Subianto (PS) tended to usedynamic linear text development pattern, whereas Joko Widodo (JW) tended to use a constant linear textdevelopment pattern.
Keywords: development system of linguistic experience; text of debate; Systemic Functional Linguistics (SFL)